Steering the AI world: an exploratory comparison of AI Acts in the EU and Canada - Zhu, Ruiyi; Tsai, Tien-I (Information Research an international electronic journal, 2025)
Introduction. As artificial intelligence (AI) continues to grow rapidly, governments are implementing legislative frameworks to address its risks and opportunities. This paper provides a comparative analysis of AI Acts in the European Union (EU) and Canada, focusing on two legislative efforts: the EU artificial intelligence act (EU AI Act) and Canada’s artificial intelligence and data act (AIDA). Method. A summative approach of qualitative content analysis was used to examine the scope, risk classification, and regulatory strategies employed in the EU AI Act and Canada’s AIDA. This study highlights similarities and differences in their approaches to managing AI’s societal impacts. Results. Both Acts provide positive directions and encourage responsible AI by addressing AI-related risks and opportunities. The analysis further explores the challenges, such as the definition of AI, enforcement mechanisms, and the inclusion of ethical considerations. Conclusion. By drawing on these cases, the paper illustrates how regulatory steering can ensure responsible AI development and deployment in different geopolitical contexts. This paper offers insights into the evolving nature of AI governance and contributes to the broader discourse on balancing innovation with societal safeguards.